Advanced paternal age: How old is too old?. Issue 10 (13th September 2006) - Bray, Isabelle; Gunnell, David; Davey Smith, George
Abstract : Average paternal age in the UK is increasing. The public health implications of this trend have not been widely anticipated or debated. This commentary aims to contribute to such a debate. Accumulated chromosomal aberrations and mutations occurring during the maturation of male germ cells are thought to be responsible for the increased risk of certain conditions with older fathers. Growing evidence shows that the offspring of older fathers have reduced fertility and an increased risk of birth defects, some cancers, and schizophrenia. Adverse health outcomes should be weighed up against advantages for children born to older parents, mindful that these societal advantages are likely to change over time.